Designers' Cognitive Thinking Based on Evolutionary Algorithms - Zhang Shutao; Jianning Su; Chibing Hu; Peng Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The research on cognitive thinking is important to construct the efficient intelligent design systems. But it is difficult to describe the model of cognitive thinking with reasonable mathematical theory. Based on the analysis of design strategy and innovative thinking, we investigated the design cognitive thinking model that included the external guide thinking of "width priority - depth priority" and the internal dominated thinking of "divergent thinking - convergent thinking", built a reasoning mechanism of design information with the thinking mathematics theory and established a product image form design model with the generalized interactive genetic algorithm. The example of testing machine form design shows that the method is reasonable and feasible. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.3804